Cross-cultural Adaptation and Validation of the Simplified-Chinese Version of Neck Bournemouth Questionnaire for Patients in Mainland China. Issue 7 (1st April 2019) - Zhang, Zi-Cheng; Jia, Zheng-Yu; Cheng, Ya-Jun; Wang, Fei; Yang, Yi-Lin; Li, Ming; Zhou, Xiao-Yi; Wei, Xian-Zhao
Abstract : Study Design: A prospective study. Objective: The aim of this study was to develop and assess the internal reliability and structure validity of a simplified Chinese version of the Neck Bournemouth Questionnaire (SC-NBQ) for evaluation of patients with nonspecific neck pain (NP) in mainland China. Summary of Background Data: The NBQ has been cross-culturally translated into several languages with good internal consistency and construct validity to evaluate low back pain and NP. However, the NBQ has been not translated or validated for Chinese-speaking patients. Methods: The SC-NBQ was developed by standard cross-translation procedures, and completed by 106 patients with nonspecific NP, along with other self-reported questionnaires, including the Neck Disability Index (NDI), Hospital Anxiety and Depression Scale (HADS), Functional Rating Index (FRI), and 36-Item Short Form Health Survey (SF-36). The internal consistency, test-retest reliability, and construct validity of the SC-NBQ were determined. Results: The NBQ was successfully translated into Chinese. All patients completed the SC-NBQ twice, and the other instruments. Score distribution demonstrated that there was no floor or ceiling effects of the SC-NBQ. Cronbach α coefficient (α = 0.89) and intraclass correlation coefficient (ICC = 0.97) showed good internal consistency and test-retest reliability. A good construct validity was shown by strong correlation with HADS ( r  = 0.75), NDI ( r  = 0.82), FRI ( r  = 0.90) and SF-36 physical functioning ( r  = 0.75), and bodily pain ( r  = 0.75) subscales. Conclusion: The SC-NBQ demonstrated good internal consistency, test-retest reliability, and construct validity, and may be used for the evaluation of NP in Chinese-speaking patients. Level of Evidence: 2 Abstract : Neck Bournemouth Questionnaire was successfully translated into a simplified Chinese version (SC-NBQ). Satisfactory internal consistency, test-retest reliability, and construct validity was shown, along with an excellent completion rate in patients in mainland China. The establishment of the SC-NBQ may assist in the evaluation of patients with nonspecific neck pain in mainland China.